(untitled) (Bulletin of Innovative Research, 2026)
This article explores recent research in the fields of literature and translation. It discusses how globalization, technology, and cultural change have affected the way we read, write, and translate texts. The article also highlights the growing importance of interdisciplinary studies, such as the use of artificial intelligence in translation and the role of literature in shaping global understanding. Finally, it reflects on the importance of literature and translation in building connections between different cultures.